PENGELOLAAN PEMBELAJARAN PAUD DALAM MENGEMBANGKAN POTENSI ANAK USIA DINI - Rozalena, Rozalena; Kristiawan, Muhammad (Graduate Program Magister Manajemen Pendidikan, 2017)
In realizing early childhood that can develop the potential of early childhood required the existence of planning, organizing, implementation, and controlling. This paper was library research. The result obtained indicate that PAUD learning activities consist of Teaching and Learning Activities, Reviewing the Education Calendar, and Learning Schedule Arrangements. Guidelines for learning organization are concerned on defining developmental stages, capacity indicators, defining the concept of knowledge introduced, setting themes, developing learning activities, preparing tools and materials. Learning planning strategy should pay attention to SKH (Daily Activities Unit) and SKM (Weekly Activities Unit). The curriculum should be structured by considering the differences which is appeared in society, then learners can recognize the diversity of social life. The setting of learning class is organized according to the schoolâs vision and mission. The teacherâs teaching activities start from welcoming the students in front of the school gate, carry out the learning, take the students to the front of the gate until the child is picked up by their respective parents. Early childhood learning activity is in the form of learning while dancing or moving; Drawing/coloring while learning; and memorize the word while clapping.Â Keywords: Learning Organizarion; PAUD; The Potential of Early Childhood